A Study by Shiro Fujimura on the Planning Intentions for the Construction of Civic Center in the Castle Town City of Kofu, Japan - Matsuura, Kenjiro (International Planning History Society Proceedings, 2024)
In Japan, as the social system underwent a transformation from the feudalistic period to the Meiji period, government office districts with a concentration of government facilities were formed in castle towns, which had been the main cities during the feudalistic period. In Kofu city, Yamanashi Prefecture, a civic center with quasi-Western-style architecture was formed by Shiro Fujimura, who was appointed as prefectural governor in 1873. The purpose of this study is to clarify the actual situation of the formation of the civic center by focusing on the Kofu civic center, which was planned by Shiro Fujimura in the early Meiji period, as well as how the spatial configuration of the castle town was read to construct public office facilities. Specifically, this study aims to 1) clarify Fujimura’s urban planning intentions based on the layout of planned and constructed government facilities, and 2) clarify the uniqueness of the Kofu civic center by comparing it with Yamagata and Utsunomiya, where planned civic centers were established by prefectural governor Michitune Mishima. The findings are as follows: 1) an L-shaped civic center was formed in front of Ote-gomon and along Tokiwa- dori in the former samurai district near the castle, with the prefectural office facing east; 2) the urban space in the civic center showed modern landscaping with street trees, waterways, road maintenance, fire prevention measures, and shared open spaces; and 3) Mishima developed a symmetrical civic center centering on the prefectural government office as a symbol of the authority of the Meiji government, while Fujimura was the first to construct a silk mill, placing importance on the development of industry, and subsequently the civic center, which was centered on the silk mill .